Clusters In the Construction of The Third Renaissance Foundation - Maryambibi Djumaniyazovna Abdullayeva (Euro Asian Journal Publishing, 2024)
This article states that on the personal initiative of the head of state, the "cluster institute" covers all areas, including the transfer of agricultural land entirely to private clusters and cooperatives, which has resulted in an average increase in cotton yields of 10 percent per year, and now, in the grain, livestock, fruit and vegetable sectors, about 500 clusters and cooperatives operate. Today, the cluster system is being implemented in higher education in order to introduce new approaches to the training and development of qualified teachers in pre-school education system in accordance with modern requirements and expected results
Keywords: clusters and cooperatives; the third renaissance; universities